Tactile Low Frequency Vibration in Dementia Management: A Scoping Review - Campbell, Elsa A.; Kantor, Jiří; Kantorová, Lucia; Svobodová, Zuzana; Wosch, Thomas (Frontiers in Psychology, 2022)
The prevalence of dementia is increasing with the ever-growing population of older adults. Non-pharmacological, music-based interventions, including sensory stimulation, have been reported by the Lancet Commission in 2020 to be the first-choice approach to managing the behavioural and psychological symptoms of dementia. Low frequency sinusoidal interventions, as those being related to music interventions through their core characteristics, may offer relief for these symptoms. Although there has been increasing attention on the effectiveness of auditory music interventions and music therapy for managing dementia, this has not included low frequency vibration. This scoping review, following the Joanna Briggs Institute methodology guidelines, was conducted to investigate participants responses to both sound and mechanical vibration, the characteristics of the delivered interventions, methodological challenges, and the specifics of the research experiments reported. An extensive search was conducted in BMC, CINAHL, Cochrane Central Register of Controlled Trials, EMBASE, ERIC, MEDLINE (OvidSP), Pedro, ProQuest Central, PsycINFO, Scopus, and Web of Science. Current Controlled Trials, Clinical Trials, and Google Scholar were also searched as well as a hand search in relevant journals. Eight full-length studies were included in the analysis and critical appraisal. Issues in quality related to, for example, control group and blinding. Few studies addressed participants’ subjective responses to the interventions. Reporting on the intervention characteristics was unclear. It appeared more frequent sessions led to better outcomes and home-based interventions potentially addressing the issue of access and feasibility. Future research should include neuroimaging to measure and confirm the hypothesised mechanism of cerebral coherence. Standardised reporting of intervention characteristics is also needed to ensure replicability of the experiments.